LABORATORY SYSTEM FOR INVESTIGATION OF FATIGUE DEGRADATION IN FERROMAGNETIC MATERIALS AND EXAMPLES OF ITS IMPLEMENTATION - V. N. Busko; D. A. Vintov (Приборы и методы измерений, 2015)
Shows the block diagram of the laboratory system for investigation of fatigue degradation in ferromagnetic materials by method of magnetic noise. Describes the principle operation of the system, given the practical results its using in assessment of the degree fatigue degradation in ferromagnetic structural steels and alloys on the basis of cyclic testing and measuring the intensity of the magnetic noise.